The how to of qualitative research - Aurini, Janice D.; Heath, Melanie; Howells, Stephanie (SAGE, 2022)
"A step-by-step introduction to doing qualitative research, this book will support you through each milestone of your research project. Whatever type of data or data collection method you use, it shows you how to navigate the nuts and bolts of qualitative research, from forming your research question to effective writing up. Your cheat sheet, roadmap, and toolbox all in one, it helps you choose the best research tools for your project while managing any challenges you might encounter with: · Guidance on putting different research designs into practice, including newer forms such as social media research · Detailed advice on managing ethical issues like data security and privacy · Practical mapping tools like checklists and quick tips · Online case studies and further reading to deepen your knowledge and expand your bibliography"--Provided by publisher.